LEARNING MODELS IN FOOTBALL PASSING: LITERATURE REVIEW STUDY - Simbolon, Yodi Ganter; Makorohim, M. Fransazeli (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
The purpose of this literature review is to review the scientific literature on the research of Learning Models in Football Passing. One database (Google Scholar) was used to select articles containing information on Learning Models in Football Passing. The search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After the exclusion criteria, only 7 articles were categorized. The results show that the types of research used in the research of Learning Models in Football Passing are diverse, namely; Research & Development (R&D) method research, Experiments using the randomized pretest-posttest control group the same subject design, classroom action (PTK), literature study research and quantitative, experiments. On average, the research uses the Research & Development (R&D) and classroom action (PTK) methods in data collection. Some limitations inherent in the review have been noted, and it is necessary to continue this study further globally with a literature review or mapping study (bibliometric and scientometric), and it is also necessary to do about the application of Learning Models in improving skills in PJOK learning and its impact, because in the current learning process, elements such as combining and modifying sports learning models can make students happier and happier when exercising, dialogue, and respect, as well as physical activity and sports, are very important.